Trelliswork and Craquelure. (October 2017) - Koenderink, Jan; van Doorn, Andrea; Wagemans, Johan
Consider a mosaic image, the edges of the tesseræ being unrelated to pictorial content. Depending upon grout color, the picture is seen as uninterrupted "behind bars" or divided into tiles by "cracks" as in an ancient oil painting. The phenomenology is explored.